2022
DOI: 10.21037/atm-22-115
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane attenuates hepatic ischemia reperfusion injury by the miR-122/Nrf2 pathway

Abstract: Background: Sevoflurane can protect organs from ischemia-reperfusion (IR) injury, but the mechanism is still unclear. is a liver-specific microRNA (miRNA) and regulates liver function.Therefore, this study aims to elucidate the relationship between the protective effect of sevoflurane and miR-122 in liver IR injury.Methods: Wistar rats were divided into the following groups: sham, IR, IR + sevoflurane, IR + miR-122 antagomir, and IR + miR-122 antagomir + sevoflurane. Hematoxylin and eosin (H&E) staining and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…IRI, the imbalance between oxidant–antioxidant processes, accompanied by excessive production of ROS, 29 can be expressed as a pathophysiological stress that develops with local and systemic inflammation caused by the inability to ensure and restore blood flow to the organ. 30 The increase in ROS and inflammatory cells in the ischemic tissue affects blood flow in the ischemic tissue, causing even more inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…IRI, the imbalance between oxidant–antioxidant processes, accompanied by excessive production of ROS, 29 can be expressed as a pathophysiological stress that develops with local and systemic inflammation caused by the inability to ensure and restore blood flow to the organ. 30 The increase in ROS and inflammatory cells in the ischemic tissue affects blood flow in the ischemic tissue, causing even more inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that they achieved this by increasing the expression of HO –1 , supporting the transport of Nrf2 from the cytoplasm to the nucleus, and decreasing the expression of miR-122 and p53. 28 Wang et al reported that sevoflurane preconditioning reduced IR-induced hepatocyte apoptosis, hepatic inflammation, and the serum levels of GST, ALT, and AST. They stated that this might be related to the inhibition of the IR-mediated down-regulation of miR-124-3p.…”
Section: Discussionmentioning
confidence: 99%
“…The prepared preparations were examined under a research microscope (Olympus CX31-Japan) and their photographs were taken at 40 X magni cation. Then, the severity of the damage was evaluated according to the Suzuki Score (Zhang et al 2022).…”
Section: Methodsmentioning
confidence: 99%